THE CRIMEAN KHANATE IN THE FOREIGN POLICY OF THE OTTOMAN EMPIRE AND THE GOLDEN HORDE (50-70 YEARS OF THE 15TH CENTURY) - К.Т. Жумaгулов; Н.М. Абдукaдыров (Journal of Oriental Studies, 2019)
In the second half of the XV century, some foreign policy directions of these two countries were tied to a single political factor that was associated with the Crimean Khanate. At this time the Crimean Khan- ate separated from the Golden Horde, trying to live independently. The Crimean rulers received political support from the Ottoman Empire. The Ottoman Empire rendered political support to the Crimean khans and established close ties with them. At this time, the Golden Horde was on the verge of decline, but the Horde rulers tried to reconnect to the Crimea. Thus, in the foreign policy of the two powers, the Crimean Khanate has become a new political factor. This scientific article is devoted to the study of foreign policy processes in the 50-70-ies of the XV century, between the Ottoman Empire and the Golden Horde in connection with the Crimean Khanate. One of the main objectives of the study is the foreign policy of the Ottoman Empire in the Crimean peninsula and in the Black Sea region. In the scientific work examines diplomatic contacts between countries, as well as analyzes the foreign policy positions and principles of the rulers of the two sides. Key words: Ottoman Empire, Golden Horde, Crimean Khanate, Crimean Peninsula, Foreign Policy, Ambassadors.